1990
DOI: 10.1111/j.1460-2695.1990.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Growth and Closure Behaviour Through a Compressive Residual Stress Field

Abstract: Behaviour of fatigue crack growth and closure through a compressive residual stress field is investigated by performing fatigue crack growth tests on welded SEN specimens of a structural steel (JIS SMSOA). Depending on the type of the initial residual stress in the region of crack growth, the growth and closure of the crack show different behaviour. In particular, in the transition region from a compressive residual stress field to a tensile residual stress field, the fatigue crack growth rates cannot be descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 18 publications
(12 reference statements)
1
32
0
4
Order By: Relevance
“…Itoh et al [5] studied the effect of residual stress on fatigue crack propagation rate in longitudinal welded residual stress field and found that the effect of crack growth rate in weld residual stress field could be evaluated in terms of the effective stress intensity range, based on the measurement of effective stress ratio and crack opening ratio. Kang et al showed [6] that the effective stress intensity factor and the effective stress ratio can be applied to predict fatigue crack growth rate in both tensile and compressive residual stress field by using base material's crack growth rate data with different stress ratio. Bucci [7] investigated the effects of residual stress on fatigue crack growth measurement.…”
Section: Early Studiesmentioning
confidence: 99%
“…Itoh et al [5] studied the effect of residual stress on fatigue crack propagation rate in longitudinal welded residual stress field and found that the effect of crack growth rate in weld residual stress field could be evaluated in terms of the effective stress intensity range, based on the measurement of effective stress ratio and crack opening ratio. Kang et al showed [6] that the effective stress intensity factor and the effective stress ratio can be applied to predict fatigue crack growth rate in both tensile and compressive residual stress field by using base material's crack growth rate data with different stress ratio. Bucci [7] investigated the effects of residual stress on fatigue crack growth measurement.…”
Section: Early Studiesmentioning
confidence: 99%
“…This is attributed to the possible partial crack opening when the crack grows in the transition region from compression to tension in the initial residual stress field. One of the authors [4,5] has investigated extensively the behaviour of fatigue crack growth through residual stress fields using welded specimen of SM 50A (JIS) steel and obtained the following results: the R'-method as well as the AK,,method can be successfully applied to predict fatigue crack growth rates through a tensile residual stress field and also through uniform compressive residual stress field. The equivalence of both methods is due to the fact that the fatigue crack growth through a tensile or uniform compressive residual stress field is essentially governed by AK,, and the behaviour of the crack opening stress intensity factor KO, is uniquely controlled by the effective stress ratio R' for a given Kmx.…”
Section: Introductionmentioning
confidence: 98%
“…From the results, it should be noted that even severe surface damage occurred during the SP treatment; this damage had no significant influence on the fatigue behavior because of the induced CRS layer [9]. Bouraoui et al [27] suggested that the degradation of the high cycle fatigue behavior of SP material is due to unfavorable surface topography changes after peening treatment, such as small micro cracks, overlaps, and scales.…”
Section: Determination Of Initial Surface Damage By Spmentioning
confidence: 96%
“…Therefore, many attempts have been made to improve fatigue lifespan [1][2][3][4] and to quantify damage growth [5][6][7][8] in these situations. In terms of fatigue lifespan extension, shot-peening (SP) is an effective tool with regards to the induced compressive residual stress (CRS) near the surface, and has strongly retarded fatigue crack growth under cyclic loads [9,10]. However, the beneficial effects of SP can decrease or disappear as a result of the residual stress relaxation phenomenon during the fatigue lifetime [3,11].…”
Section: Introductionmentioning
confidence: 99%